2022
DOI: 10.1186/s13578-021-00739-6
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of RORγt+ cells in the intestine of newborns and its role in the development of experimental necrotizing enterocolitis

Abstract: Background Neonates possess an immature and plastic immune system, which is a major cause of some diseases in newborns. Necrotizing enterocolitis (NEC) is a severe and devastating intestinal disease that typically affects premature infants. However, the development of intestinal immune cells in neonates and their roles in the pathological process of NEC have not been elucidated. Results We examined the ontogeny of intestinal lamina propria lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Fetus-derived CD4 + T -cells preferentially produce Th2 cytokines when stimulated with low amounts of antigen ( 216 , 217 ). Antigenic encounters in the phase before weaning (the window of opportunity) have the ability to induce the differentiation of neonatal CD8 + T -cells to RORγt + Tregs ( 218 , 219 ). Upon re-exposure to the same antigen later in life, the infant is more likely to elicit a more tolerant immune reactivity ( 220 ).…”
Section: Postnatal Immunitymentioning
confidence: 99%
“…Fetus-derived CD4 + T -cells preferentially produce Th2 cytokines when stimulated with low amounts of antigen ( 216 , 217 ). Antigenic encounters in the phase before weaning (the window of opportunity) have the ability to induce the differentiation of neonatal CD8 + T -cells to RORγt + Tregs ( 218 , 219 ). Upon re-exposure to the same antigen later in life, the infant is more likely to elicit a more tolerant immune reactivity ( 220 ).…”
Section: Postnatal Immunitymentioning
confidence: 99%
“…Drosophila Toll was discovered as a receptor for dorso-ventral patterning during development and was later identified as a participant in immunity against fungal infections ( 84 ). Consequently, several other homologues of Toll, named Toll-like receptors (TLRs) were discovered in mammals.…”
Section: Immunological Status Of Infants With Necmentioning
confidence: 99%
“…Additionally, retinoic acid-induced polarization of CD4 + T cells towards Treg from Th17 resulted in reduced NEC severity ( 123 ). Furthermore, Zhao et al reported an increased percentage of RORγt + cells (inflammatory Th17 and type 3 innate lymphoid cell populations) in the intestinal lamina of mice and humans with NEC compared to those without NEC ( 84 ). Studies have also demonstrated a significant decrease in lamina propria associated Treg cells in surgical NEC specimens ( 85 , 86 , 89 ).…”
Section: Immunological Status Of Infants With Necmentioning
confidence: 99%
“…Maintaining an appropriate balance between the tolerogenic IL-22 and proinflammatory IL-17 is necessary for enabling GALT to distinguish between gut commensals and pathogens [66]. For example, GALT dyshomeostasis, due to dysfunctional ILC3 and an impaired Tregs/Th17 ratio, was demonstrated to trigger food allergies and IBD [67][68][69].…”
Section: Introductionmentioning
confidence: 99%